Business Information Systems and Technology 4.0 New Trends in the Age of Digital Change (Studies in Systems, Decision and Control,, 2018)
This book discusses digitalization trends and their concrete applications in business and societal contexts. It summarizes new findings from research, teaching and management activities comprising digital transformation, e-business, the representation of knowledge, human-computer interaction and business optimization. The trends discussed include artificial intelligence, virtual reality, robotics, blockchain, and many more. Professors and researchers who conduct research and teach at the interface between academia and business present the latest advances in their field. The book adopts the philosophy of applied sciences and combines both rigorous research and practical applications. As such, it addresses the needs of both professors and researchers, who are constantly seeking inspiration, and of managers seeking to tap the potential of the latest trends to take their business to the next level. Readers will find answers to pressing questions that arise in their daily work.